Staphylococcus aureus δ-toxin present on skin promotes the development of food allergy in a murine model - Yamada, Hiromichi; Kaitani, Ayako; Izawa, Kumi; Ando, Tomoaki; Kamei, Anna; Uchida, Shino; Maehara, Akie; Kojima, Mayuki; Yamamoto, Risa; Wang, Hexing; Nagamine, Masakazu; Maeda, Keiko; et al. (Frontiers in Immunology, 2023)
BACKGROUND: Patients with food allergy often suffer from atopic dermatitis, in which Staphylococcus aureus colonization is frequently observed. Staphylococcus aureus -toxin activates mast cells and promotes T helper 2 type skin inflammation in the tape-stripped murine skin. However, the physiological effects of -toxin present on the steady-state skin remain unknown. We aimed to investigate whether -toxin present on the steady-state skin impacts the development of food allergy. MATERIAL AND METHODS: The non-tape-stripped skins of wild-type, KitW-sh/W-sh, or ST2-deficient mice were treated with ovalbumin (OVA) with or without -toxin before intragastric administration of OVA. The frequency of diarrhea, numbers of jejunum or skin mast cells, and serum levels of OVA-specific IgE were measured. Conventional dendritic cell 2 (cDC2) in skin and lymph nodes (LN) were analyzed. The cytokine levels in the skin tissues or culture supernatants of -toxin-stimulated murine keratinocytes were measured. Anti-IL-1 antibody-pretreated mice were analyzed. RESULTS: Stimulation with -toxin induced the release of IL-1, but not IL-33, in murine keratinocytes. Epicutaneous treatment with OVA and -toxin induced the local production of IL-1 This treatment induced the translocation of OVA-loaded cDC2 from skin to draining LN and OVA-specific IgE production, independently of mast cells and ST2. This resulted in OVA-administered food allergic responses. In these models, pretreatment with anti-IL-1 antibody inhibited the cDC2 activation and OVA-specific IgE production, thereby dampening food allergic responses. CONCLUSION: Even without tape stripping, -toxin present on skin enhances epicutaneous sensitization to food allergen in an IL-1-dependent manner, thereby promoting the development of food allergy.